2022
DOI: 10.2334/josnusd.22-0221
|View full text |Cite
|
Sign up to set email alerts
|

The 3-year cumulative survival rates of posterior monolithic zirconia crowns and their antagonist teeth, and their influencing factors

Abstract: Purpose:The purpose of this study was to evaluate the 3-year cumulative survival rates of posterior single monolithic zirconia crowns (MZCs) and their antagonists, and to analyze the influencing factors. Methods: The clinical outcomes of posterior single MZCs and their abutment teeth with antagonists, and the antagonists between April 2014 and September 2020 were evaluated retrospectively. The 3-year cumulative survival rates were calculated and associations between the survival time and predictor variables ("… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Patient satisfaction was high, and periodontal conditions were comparable to measured values before crown delivery [ 23 ]. There are other studies by Goto et al [ 24 ], Badr et al [ 14 ], Guncu et al [ 15 ], Waldecker et al [ 25 ], Gao et al [ 26 ], Gseibat et al [ 27 ]; Cakan and Özcan [ 28 ], Hosseini et al [ 29 ] and Le et al [ 30 ] that were conducted recently, but were of shorter follow-up duration.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction was high, and periodontal conditions were comparable to measured values before crown delivery [ 23 ]. There are other studies by Goto et al [ 24 ], Badr et al [ 14 ], Guncu et al [ 15 ], Waldecker et al [ 25 ], Gao et al [ 26 ], Gseibat et al [ 27 ]; Cakan and Özcan [ 28 ], Hosseini et al [ 29 ] and Le et al [ 30 ] that were conducted recently, but were of shorter follow-up duration.…”
Section: Discussionmentioning
confidence: 99%
“…LD ceramic is considered the material of choice for the fabrication of posterior and anterior restorations because of its superior mechanical and esthetic properties [ 11 , 12 ]. Previous studies reported that LD ceramics showed comparable 5-year survival rates to those of zirconia when used for the fabrication of posterior crowns and fixed partial dentures [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%